The Macedonian issue in political bargaining in the Balkans in the last decade of the 20th century - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2009)
The author of the article addresses the issue of disputes over the name and heritage of Macedonia, which have become one of the key factors destabilising international relations in South-Eastern Europe after the break-up of Yugoslavia. The background to this was a historical and symbolic rivalry in which the Greeks, Macedonians, Bulgarians and, to some extent, Serbs have claimed rights to the traditions of ancient and medieval Macedonia, making it part of their own national identity. The aim of the study is to show how the dispute over the name of the Macedonian state and related symbolic issues (flag, constitution, historical narratives) has been used as a political and economic tool, especially in Greek-Macedonian relations. An analysis of historical sources, international documents, press and literature on the subject, both Greek and Macedonian, was carried out. The conclusions indicate that the ‘Macedonian problem’ went beyond a semantic dispute, becoming an arena for the clash of two nationalisms – Greek, rooted in the 19th-century idea of exclusivity to the heritage of Macedonia, and Macedonian, striving for recognition of a separate state and national identity. This dispute illustrates the nature of contemporary political relations in the Balkans, where historical memory and national symbols play an important role in shaping current politics.